2003
DOI: 10.1128/mcb.23.24.9245-9250.2003
|View full text |Cite
|
Sign up to set email alerts
|

While K-ras Is Essential for MouseDevelopment, Expression of the K-ras 4A Splice VariantIsDispensable

Abstract: In mammals, the three classical ras genes encode four highly homologous proteins, N-Ras, H-Ras, and the isoforms K-Ras 4A and 4B. Previous studies have shown that K-ras is essential for mouse development and that while K-ras 4A and 4B are expressed during development, K-ras 4A expression is regulated temporally and spatially and occurs in adult kidney, intestine, stomach, and liver. In the present study, the pattern of K-ras 4A expression was examined in a wide range of wild-type adult mouse tissues, and gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
90
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 31 publications
4
90
0
1
Order By: Relevance
“…However, it was identified that K-Ras functions as a major regulator of Akt activation in erythroid differentiation [33]. Furthermore, K-Ras is required in development of mouse embryos [34,35], indicating that K-Ras performs specific functions that cannot be carried out by either H-Ras or N-Ras during embryogenesis. Our observations also indicate that knockdown of N-Ras during differentiation induces significantly higher levels of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was identified that K-Ras functions as a major regulator of Akt activation in erythroid differentiation [33]. Furthermore, K-Ras is required in development of mouse embryos [34,35], indicating that K-Ras performs specific functions that cannot be carried out by either H-Ras or N-Ras during embryogenesis. Our observations also indicate that knockdown of N-Ras during differentiation induces significantly higher levels of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…GAPs stimulate the intrinsic GTPase activity of Ras 10,000-fold, oncogenic Ras mutations interfere with the ability of GAPs to interact with Ras producing constitutively active Ras proteins. In the same way that multiple GEFs have been identified, 8 GAPs have been characterised providing a range of possibilities for initiating down-regulation of Ras signalling.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In addition, knockout mice revealed essential roles for K-Ras in development, while H-and N-Ras appeared dispensible for mouse embryogenesis. [16][17][18][19] Along these lines, defects in human development have recently been associated with Ras isoform-specific functions. [19][20][21] The different magnitude of oncogenic Ras isoform signaling further supports signal specificity of Ras isoforms.…”
Section: Functional Differences Of Ras Isoforms and Differential Gap mentioning
confidence: 99%